Algorithms for recovery of sparse signals in compressed sensing - Tran, Anh Vu. (2013)
In real-world applications, most of the signals can be approximated by sparse signals. When dealing with sparse or compressible signal, the traditional process of acquiring the signal and then discard most of the samples for compression is inefficient and memory consuming. Recent developments in statistics and signal processing have introduced the method of compressed sensing as an efficient reconstruction of sparse signals based on incomplete set of measurements.